(untitled) (Editora Impacto Científico, 2025)
This chapter explores the potential of urban green areas as strategic educational spaces, using the Santa Marta and Cambuí forests in São Carlos-SP as references. It presents environmental education experiences conducted both in-person and through distance learning, highlighting the integration between civil society, schools, universities, and public authorities. Ecological benefits, pedagogical practices, documentation and content digitization strategies are discussed, along with proposals for sustainable management, educator training, and community and private sector engagement. The experience demonstrates how urban green areas can become true laboratories for socio-environmental education, combining theoretical learning and practical experiences in a dynamic and participatory way. DOI: https://doi.org/10.56238/edimpacto2025.090-054